Insertion-Related Pain and Short-Term Satisfaction With Two Copper IUDs: A Randomized Trial [22I]. (May 2020) - Burke, Anne E.; Edelman, Alison; Chen, Beatrice A.; Castano, Paula; Chen, Pai-Lien
Abstract : INTRODUCTION: Pain during intrauterine device (IUD) insertion is a barrier to uptake. We compared insertion-related pain and short-term satisfaction between two copper (Cu) IUDs. METHODS: We conducted a multicenter, single-blind randomized trial comparing two CuIUDs. Participants were randomized (4:1 ratio) to a smaller (Mona Lisa NT Cu380-Mini [24 mm x 30 mm]) or standard (Paragard TCu380A [32 mm x 36 mm]) CuIUD. Participants recorded maximum pain levels on a 10 cm visual analog scale at nine timepoints (pre- and immediately post-IUD insertion, daily for 7 days). At day 7, participants reported overall satisfaction (5-point scale) and whether they would recommend the product to others. For each timepoint, we computed mean pain level and mean change in pain from baseline, and stratified by parity. We used T-tests and chi-square tests to compare results between products. RESULTS: We enrolled 1, 105 women, 84% nulliparous (n=924). Mean pain levels immediately post-insertion were 4.9 cm (SD 2.3) for both the smaller (n=886) and standard (n=219) products. Subsequent pain levels decreased equally across both products, from 2.5 cm (day 2) to 0.7 cm (day 7). Mean pain after baseline adjustment was similar between products. Nulliparous women using either IUD reported higher pain levels at all timepoints than parous women ( P< .05). Among nulliparous women, 54% were highly satisfied with the smaller versus 45% with standard IUD ( P< .05); over 92% using each product would recommend it. Parous women reported similar satisfaction by product. CONCLUSION: Reported pain was similar between IUDs. Satisfaction among nulliparous women was higher at 7 days with a smaller CuIUD. Longer-term data may elucidate possible differences between products.